2004
DOI: 10.1210/en.2003-0602
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Modulates Behavioral Responses to Sweet Substances by Influencing Peripheral Taste Structures

Abstract: Leptin is a hormone that regulates body weight homeostasis mainly via the hypothalamic functional leptin receptor Ob-Rb. Recently, we proposed that the taste organ is a new peripheral target for leptin. Leptin selectively inhibits mouse taste cell responses to sweet substances and thereby may act as a sweet taste modulator. The present study further investigated leptin action on the taste system by examining expression of Ob-Rb in taste cells and behavioral responses to sweet substances in leptin-deficient ob/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
124
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(130 citation statements)
references
References 28 publications
3
124
1
2
Order By: Relevance
“…Injection of leptin into lean mice resulted in suppressed response to sweet tastants in peripheral taste nerves without effect on other taste qualities. 80 Shigemura et al 81 demonstrated that the functional leptin receptor Ob-Rb messenger RNA is expressed in the fungiform and circumvallate taste buds in mice and that the presence or absence of Ob-Rb was associated with differences in leptin's effect on behavioral response to sweet substances. Leptin receptor-deficient obese mice showed increased gustatory neural response to sweet compounds.…”
Section: Leptinmentioning
confidence: 99%
“…Injection of leptin into lean mice resulted in suppressed response to sweet tastants in peripheral taste nerves without effect on other taste qualities. 80 Shigemura et al 81 demonstrated that the functional leptin receptor Ob-Rb messenger RNA is expressed in the fungiform and circumvallate taste buds in mice and that the presence or absence of Ob-Rb was associated with differences in leptin's effect on behavioral response to sweet substances. Leptin receptor-deficient obese mice showed increased gustatory neural response to sweet compounds.…”
Section: Leptinmentioning
confidence: 99%
“…It has been shown by Shigemura et al (2004) that leptin suppresses response to sweet taste stimuli in mice. Leptin is a hormone regulating body weight homeostasis via hypothalamic functional leptin receptor and is elevated in obese compared to lean subjects (Shigemura et al, 2004).…”
Section: )mentioning
confidence: 99%
“…It has been shown by Shigemura et al (2004) that leptin suppresses response to sweet taste stimuli in mice. Leptin is a hormone regulating body weight homeostasis via hypothalamic functional leptin receptor and is elevated in obese compared to lean subjects (Shigemura et al, 2004). Another study also suggested a negative relationship between pleasantness ratings for sweet stimuli and obesity (Thompson et al, 1976;Kamphuis and Westerterp-Plantenga, 2003).…”
Section: )mentioning
confidence: 99%
“…Transcripts of DC from normal mice displayed a product of correct size (413 bp) for functional Ob-Rb, whereas those from db/db DC showed a larger product (519 bp) due to the gene targeting with an insertion [14][15][16]. The identities of these products were confirmed by sequencing, which showed an abnormal insertion (106 bp) with a stop codon within the coding region for the intracellular domain of Ob-Rb present in db/db DC, as previously reported for other tissues [14][15][16]. Furthermore, flow cytometric analysis confirmed the positive labeling of surface Ob-R on DC from normal control mice (Fig.…”
Section: Expression Of Ob-r In Primary and Bm-derived DCmentioning
confidence: 99%